PENDAYAGUNAAN PLATFORM DIGITAL DALAM PEMASARAN PRODUK UMKM DESA GLAGAH - Rohmah, Siti Maftukhatur; Aulia , Anisa Rahma; Prameswari, Cindy Ashilah; Irawan, M. Izudin Fathin Alfian; Hamidah , Nabila Nur; Nugroho , Wahyu Dwi; Iksan, Iksan (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
Community service in Glagah Village, Banyuwangi, focuses on using digital platforms to market MSME products. By implementing digital marketing, MSMEs can expand market reach and increase income. The Participatory Action Research (PAR) method was used in community service in this research, starting with the inculturation stage then continuing with Mapping, making flow diagrams to hope trees and problem trees. The programs implemented include outreach, digital marketing training, content creation, and assistance in using e-commerce platforms. The results show increased product visibility online and the development of more professional branding. This not only increases the efficiency of MSME businesses but also strengthens the local economy and maintains local wisdom in processing traditional products. In the current era of globalization of the digital economy, this step is vital to increase the competitiveness of MSMEs and ensure their sustainability in an increasingly competitive market.